The RNA-binding protein RBM47 is a novel regulator of cell fate decisions by transcriptionally controlling the p53-p21-axis - Radine, Claudia (Cell Death Differ, 2019)
In recent years it has become more and more apparent that the regulation of gene expression by RNA-binding proteins (RBPs) is of utmost importance for most cellular signaling pathways. RBPs control several aspects of RNA biogenesis including splicing, localization, stability, and translation efficiency. One of these RBPs is RBM47 that recently has been suggested to function as a tumor suppressor as it was shown to suppress breast and colon cancer progression. Here we demonstrate that RBM47 is an important regulator of basal and DNA damage-induced p53 and p21(WAF1/CIP1) protein expression. Knockdown of RBM47 by siRNAs results in a strong reduction in p53 mRNA and protein levels due to an impaired p53 promoter activity. Accordingly, overexpression of Flag-RBM47 enhances p53 promoter activity demonstrating that RBM47 regulates p53 at the transcriptional level. By controlling p53, knockdown of RBM47 concomitantly decreases also p21 expression at the transcriptional level, driving irradiated carcinoma cell lines from different entities into cell death rather than into senescence. Thus, RBM47 represents a novel molecular switch of cell fate decisions that functions as a regulator of the p53/p21-signaling axis.